2011
DOI: 10.5657/kfas.2011.0325
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Nonylphenol-degrading Microbial Consortium

Abstract: Nonylphenol (NP), which is well known as an endocrine disrupter, has been detected widely in untreated sewage or waste water streams. Given the necessity of discovering an eco-friendly method of degrading this toxic organic compound, this study was conducted to isolate NP-degrading microorganisms from the aqueous environment. NPdegrading microbes were isolated through NP-containing enrichment culture. Finally, a microbial consortium, SW-3, capable of degrading NP with high efficiency, was selected from the mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The extension of the degradation process has been reported as temperature dependent [6, 42]. In this study degradation was close to 65% at 27°C; similar values have been reported by other authors [6, 40, 41, 43]. …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The extension of the degradation process has been reported as temperature dependent [6, 42]. In this study degradation was close to 65% at 27°C; similar values have been reported by other authors [6, 40, 41, 43]. …”
Section: Resultssupporting
confidence: 90%
“…Finally, a mixture culture of Yas1/Yas2 in 1% NPEO 15 medium, pH 8, showed a synergistic effect on the bacterial growth, reaching maximal values (0.095 au) at 9 h incubations and 27°C, which represents a stimulatory average factor close to 5.7 with respect to the individual bacterial cultures at 1% NPEO 15 medium (0.014 and 0.02 au); additionally, the lag phase was absent (see Figure 4). This stimulatory effect is probably due to NPEO x cometabolism by the Yas1/Yas2 system, as it has been described for other bacterial consortiums [41]. …”
Section: Resultsmentioning
confidence: 59%
“…No reports have been published regarding NP bioremediation in aquatic environments. Therefore, this study isolated NP-degrading bacteria from the microbial consortium SW-3, which was previously isolated from an aqueous environment (Song et al, 2011). We also performed a kinetic analysis of NP degradation by individual and groups of bacterial strains.…”
Section: Resultsmentioning
confidence: 99%
“…To isolate NP-degrading bacteria from the NP-degrading microbial consortium SW-3 (Song et al, 2011), the consortium strain was cultivated in YNB medium containing 100 ppm NP at 25°C under aerobic conditions. 100 uL of the culture was taken at intervals and spread on YNB agar plates containing 100 ppm NP.…”
Section: Isolation and Culture Of Np-degrading Bacteriamentioning
confidence: 99%
See 1 more Smart Citation